If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -5 = 6(3x + 8) Reorder the terms: -5 + x = 6(3x + 8) Reorder the terms: -5 + x = 6(8 + 3x) -5 + x = (8 * 6 + 3x * 6) -5 + x = (48 + 18x) Solving -5 + x = 48 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. -5 + x + -18x = 48 + 18x + -18x Combine like terms: x + -18x = -17x -5 + -17x = 48 + 18x + -18x Combine like terms: 18x + -18x = 0 -5 + -17x = 48 + 0 -5 + -17x = 48 Add '5' to each side of the equation. -5 + 5 + -17x = 48 + 5 Combine like terms: -5 + 5 = 0 0 + -17x = 48 + 5 -17x = 48 + 5 Combine like terms: 48 + 5 = 53 -17x = 53 Divide each side by '-17'. x = -3.117647059 Simplifying x = -3.117647059
| (x/9)*6 | | 6y=-6x-4 | | -2(4+5n)-5=-83 | | 5x-15-6x=6-6x/54 | | 1.4(1+0.5x)=-7 | | -16=-11-5(2a-3) | | 5x-15-6x=6-x/9 | | 2(g-2)-4=2(2g-3) | | 3.50x+36=5x | | -6=-2/x | | a=-10.6-1.5a | | 2x-16=2x-8 | | 10.3x+1=2x+4 | | 2lnx-ln(2x-7)=ln(9x)-ln(x-2) | | -14k^2-280=0 | | 3z-1z+2z-30=70 | | x+10=-100 | | 9x+10=8+8x | | 5/(x-4)=0 | | -2(2x-5)=2(X-7) | | 3y-1z+2z-30=70 | | -10x^2+22x+12=0 | | 13=p-(-15) | | 5x(4-x)=9-(x-6) | | -10y-5y=120 | | 2cos(0.5)-1=0 | | 7=b+2 | | r^2-10x-50=0 | | -6x-1x=56 | | -4/4=x | | 96x-9/2x^2 | | 2x^2-7x-16=0 |